DOES A SUSTAINABLE SUPPLY CHAIN ENHANCE MANUFACTURING COST PERFORMANCE? - Manik, Saham April; Kurniawati, Kurniawati; Masnita, Yolanda (ITB AAS Indonesia Surakarta, 2025)
Measuring the effect of SSCM practices on financial performance in manufacturing companies in Indonesia.This study surveyed 296 employees working in manufacturing companies to examine the relationship between variables.Â In this study, a quantitative approach was used with a sampling method using quantitative descriptive techniques using a questionnaire survey. For data analysis, this study used Structural Equation Modeling (SEM) with a selection of 296 employees in Manufacturing Companies with the help of the AMOS program.Â The conceptual framework proposed in this model is an adaptation and synthesis of various previous research findings conducted in developed countries. Therefore, to find out whether SSCM practices from production to distribution are economically beneficial in developing countries such as Indonesia. So this research will explore the effect of Sustainable Supply Chain Management on Financial Performance, especially in manufacturing companies in Indonesia.Retrievedthat this research can contribute to manufacturing companies as a consideration in implementing sustainable supply chain practices. This research can be useful for manufacturing industries that need to change traditional supply chain management into SSCM. In an environment with limited resources in Indonesia. This will allow the benefits of SSCM practices to be reaped in long-term probability and financial performance in the context of the economy in Indonesia.Â The sample of this study was limited to manufacturing companies with regard to financial performance and no consideration was given to other sectors such as the service sector. Therefore, future research could examine the applicability of the findings from this investigation to manufacturing companies with regard to environmental and social performance as well as with regard to the service sector and other sectors.